Cobalt(II) and nickel(II) complexes with djenkolic acid - Corbi, P. P. [UNESP]; Cavicchioli, M. [UNESP]; Mel'nikov, P. [UNESP]; Massabni, A. C. [UNESP]; De Oliveira, L. A.A. [UNESP] (My University, 2000)
Cobalt(II) and nickel(II) djenkolates CoC7H12N2O4S2 · H2O (I) and NiC7H12N2O4S2 · H2O (II) were synthesized by the reaction of potassium djenkolate with the respective chlorides. IR spectra suggested coordination via the COO- and NH2 groups for the ligands in both compounds. Visible absorption spectra confirmed the octahedral structure of the complexes. X-ray powder diffraction patterns were indexed in the orthorhombic and monoclinic unit cells with parameters: a = 11.35, b = 7.35, c = 6.85 Å for I and a = 11.54, b = 7.45, c = 6.90 Å, β = 94.95°for II.